2013
DOI: 10.1038/jid.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizing Agents and the Risk of Non-Melanoma Skin Cancer: A Population-Based Case–Control Study

Abstract: It is well-known that ultraviolet (UV) light exposure and a sun sensitive phenotype are risk factors for the development of non-melanoma skin cancer (NMSC), including basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). In this New Hampshire population-based case-control study, we collected data from 5,072 individuals, including histologically-confirmed cases of BCC and SCC, and controls via a personal interview to investigate possible associations between photosensitizing medication use and NMSC. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 18 publications
7
118
0
10
Order By: Relevance
“…There have been reports a significant increase in the risk of squamous cell carcinoma, basal cell carcinoma, and early-onset basal cell carcinoma in individuals who had used photosensitizing medication [32,33]. They show a 1.3 increase in odds of SCC with diuretic use, supporting a previously quoted 1.6 odds increase of SCC with diuretic use.…”
Section: Eyelidsupporting
confidence: 51%
See 1 more Smart Citation
“…There have been reports a significant increase in the risk of squamous cell carcinoma, basal cell carcinoma, and early-onset basal cell carcinoma in individuals who had used photosensitizing medication [32,33]. They show a 1.3 increase in odds of SCC with diuretic use, supporting a previously quoted 1.6 odds increase of SCC with diuretic use.…”
Section: Eyelidsupporting
confidence: 51%
“…However, other studies show no relation, thus CV disease may be a confounding variable. Robinson et al reported a link with tetracycline use and BCC risk [33]. The link needs to be further studied, but the consensus is to take special care in patient education with use of these agents.…”
Section: Eyelidmentioning
confidence: 99%
“…An approximation of the relative risk, known as an odds ratio, can be calculated (Mann, 2003). Robinson et al (2013) identified patients with NMSC (cases) matched by age and gender to a population of control subjects within the same geographic region. Subjects were assessed for use of photosensitizing medications and odds ratios were calculated.…”
Section: Case-control Studiesmentioning
confidence: 99%
“…Subjects were assessed for use of photosensitizing medications and odds ratios were calculated. This allowed the authors to postulate that the risk of developing certain skin cancers was enhanced by use of these medications (Robinson et al, 2013).…”
Section: Case-control Studiesmentioning
confidence: 99%
“…20/100.000 Behandlungsjahre), sodass erst nach der 1-jährigen Behandlung mehrerer 1000 RA-Patienten mit einer zusätzlich therapieinduzierten Melanomerkrankung gerechnet [11] werden muss und die generell positive Nutzen-Risiko-Bilanz der TNFBlockade nicht beeinträchtigt erscheint. [22]. Die oben erwähnte MedicareStudie [21] ergab auch, dass eine TNFInhibitor-Therapie mit einem numerisch leicht erhöhten, aber statistisch nicht signifikanten NMSC-Risiko behaftet war.…”
Section: Introductionunclassified